REPRODUCTION OF KAKEBYARAN ART IN MATARAM CITY, WEST NUSA TENGGARA - YUDARTA, I GEDE; Kusuma, Nyoman Weda; Dibia, I Wayan; Parimartha, I Gde (E-Journal of Cultural Studies, 2016)
Kakebyaran art is a performing art with the Balinese identity; it is not only popular in Bali but also in the other provinces in Indonesia and different parts of the world. In Indonesia, such a performing art is also performed in Mataram City, West Nusa Tenggara. The policy with the jargon “Maju, Religious and Berbudaya” (Being Developed, Religious, and Cultured),  which was issued by the ruler of Mataram City, affirms that the development in Mataram City is oriented toward the Islamic religious values, meaning that the other religious and cultural symbols are reduced. Such a situation has motivated the Balinese ethnic community to develop its art, tradition, and culture in general and the kekebyaran art in particular. Such a phenomenon is a domain of cultural studies which is very interesting to be explored in depth. There are three problems related to such a phenomenon. They are 1) the form and function of the reproduction of the kekebyaran art, 2) the factors contributing to the reproduction of the kekebyaran , 3) the impact of the reproduction of the kekebyaran art on and its meaning to the society of Mataram City, West Nusa Tenggara. The present study was conducted using the qualitative method, in accordance with the scientific norm and paradigm of cultural studies. Three theories were used to analyze such problems; they are the theory of cultural reproduction, the theory of identity, and the theory of semiotics. They were eclectically used to discuss the substance of the topic of discussion. The results of analysis were formulated as follows: first, the form of the reproduction of the kekebyaran art is made up of musicality, the instrumental form, the way of presenting it, its function as part of a ritual and a performing art, and its function to strengthen the local culture. Second, the factors contributing to the reproduction of the kakebyaran art are as follows:  the culture, economy and cultural communication. Third, the impact and meaning of the reproduction of the kakebyaran art are as follows:  the spiritual impact, the socio-cultural impact, the economic impact, the aesthetic meaning, and the cultural meaning.